Pandangan Islam Terhadap Tanggung Jawab Social Pelaku Bisnis (Perusahaan) Bagi Kesejahteraan Social (Studi Kasus Toko Sinar Bulan) - Fitri Kumala Sari; Vivi Afri Ani; Nur Fadilla Dilla (Jurnal Ekonomi Bisnis Syariah, 2019)
Business responsibility is essentially the responsibility of business people to Allah SWT. This can be achieved if all business actions are intended only for worship to Allah SWT. As a derivative, business activities are carried out to seek profit so that business life can continue through consumer satisfaction based on Islamic sharia. Thus the business social responsibility is actually the responsibility of the business person to the company owner, to the community, and finally to Allah SWT. Theoretically, companies must conduct their business ethically and morally and socially responsible for the company's internal and external environment. Normatively the responsibility of social and environmental companies has been regulated in the laws and regulations. In the context of Islamic law, the responsibility of business people (both individuals and business entities) towards the environment cannot be separated from the fiqh al Bi'ah, both the utilization and social welfare. The form of responsibility of business actors towards the environment in general, namely; In doing business other than shari'ah control, in taking company policy, it must be based on shariah principles and benefit elements. This includes considering Hifdzu al Bi'ah, so as to create prosperity and the survival of life